Kepuasan Masyarakat : Perubahan Minat Beli Konsumen Terhadap Manajemen Bisnis Online - Ahmad Fawaiz (Master Manajemen, 2024)
Online business is starting to be used frequently by the public. However, from the many online businesses, many entrepreneurs are still unable to carry out proper development of their online businesses. Things like attracting consumer buying interest by increasing consumer satisfaction are still not understood by some entrepreneurs. So it is necessary to carry out further research development on online business management that has an impact on increasing consumer satisfaction by looking at changes in consumer buying interest. The research method used is library research, where this is to find findings that need to be concluded and find new things so that it is easier for subsequent research to conduct research. The results are still a gap between the research results and the existing theory between the relationship between consumer buying interest and consumer satisfaction, online business management with consumer satisfaction, and online business management with consumer buying interest. Another thing that needs to be done is further research on the relationship between the three variables.